Al-Adrawi, Abdul Rahman. “Maqāṣid Application in the Khaldūnian Methodology,” Year 13, Issue 50 (Fall 1428 AH/ 2007 CE), Pp. 175-212. - العضرواي عبد الرحمن (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2007)
Abdul Rahman al-Adrawi’s article is a study of the maqāṣid (objectives of Shariʿah) methodology of Ibn Khaldūn in his theory regarding ʿumrān (human civilizational development), in which he demonstrates his independence in ijtihad and that he is a maqāṣidī philosopher who adopts an evidence-based and inductive approach. The introduction discusses al-Shāṭibī, Ibn Khaldūn and the maqāṣid approach to the Islamization of knowledge. It then discusses the concept of Ibn Khaldūn’s maqāṣid application, his theory on ʿumrān, and manifestations of maqāṣid application in the Khaldūnian methodology. It concludes with a discussion of the methodological shift that Ibn Khaldūn had caused in maqāṣid theory.